Perception and Perceived Experiences about Prevention and Consequences of Teenage Pregnancy and Childbirth among Teenage Mothers: A Qualitative Study - Bhandari, Sushila Devi; Joshi, Sarala (Journal of Advanced Academic Research, 2017)
Teenage pregnancy and childbirth is a social problem in many Asian countries including Nepal. Many quantitative studies have been done on teenage pregnancy, its outcomes, and challenges faced by teenager, but very little are known about their perceptions and experiences about teenage pregnancy and their consequences during childbirth. This study aimed to explore the perceptions and experiences of teenage pregnancy and childbirth among teenage mothers. This study has adopted phenomenology approach to explore the perceptions and experiences of being a teen mother. Study was based on data collected through in-depth interviews (IDIs), and Focus Group Discussion (FGDs). All respondents provided verbal as well as written consent to face the interview. IDI guide was used to collect information among teenage mothers to assess their perception and experiences on teenage pregnancy and childbirth. Similar guide was used for FGDs. Collected information was manually processed through qualitative content analysis and grouped into theme and subthemes. The teenage mother understood that teenage pregnancy and childbirth is a risk for both mother and child. A majority of them perceived that low education, poverty, love marriage, family problems, in-laws pressure; cultural prospects are aggravating factors leading to teenage pregnancy. Almost all of the respondents mentioned the negative impact of teenage pregnancy on the health. But very few respondents knew advantages of teenage childbirth. Most of them however knew that the teenage pregnancy can be prevented. Access to family planning services to teenage mothers, community awareness, and government support is needed to reduce teenage pregnancy and childbirth.